1976
DOI: 10.1016/0002-9378(76)90528-7
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effect of amniofetography on fetal thyroid function

Abstract: is (i v tiliiahlt' taul far thc diagnosis oj Jcltil malformations. Ttm technique is being used routinely in pregnancies carrying a high risk of externat fetal malf>rmnti(ins. Therc nrr l'en few puhlished data conierning the effect nf radiopaque dycs, conldining large amounis of iodide, on fetal thyroid function. Wc ha v c perfonned séri a i détermin a tions of sérum thyroiropin a nd thyroxine in seven newborn inf a nts to a .ssess the effect of a mniofetogra phy on feta l thyroid function. This work demomtr a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 3 publications
0
33
0
1
Order By: Relevance
“…Recent studies showed normal thyroid functions in the infants of mothers who received iodide contrast during pregnancy (25,26). Amniofetography with iodine containing contrast also Transl Pediatr 17;6(4):349-358 tp.amegroups.com induces transient CH (27).…”
Section: Fetal Iodine Exposurementioning
confidence: 99%
“…Recent studies showed normal thyroid functions in the infants of mothers who received iodide contrast during pregnancy (25,26). Amniofetography with iodine containing contrast also Transl Pediatr 17;6(4):349-358 tp.amegroups.com induces transient CH (27).…”
Section: Fetal Iodine Exposurementioning
confidence: 99%
“…Studies in animal models and case reports in humans have shown that iodinated contrast agents can cross the placenta and enter the foetus [22][23][24][25][26][27]. It is postulated that the iodinated contrast that enters the foetal circulation is excreted by the kidneys into the amniotic fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Transient hypothyroidism was observed af ter intrauterine application of contrast agents and after neonatal angiocardiography [1][2][3] and after skin disinfection with iodinecontaining solutions [4][5][6]. In other studies, however, no thyroid dysfunction was found after application of iodine-containing prepa rations in neonates [7][8][9][10], These discrepan-…”
mentioning
confidence: 86%